2018
DOI: 10.1111/jch.13387
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in adherence to antihypertensive treatment in patients aged above 55: The French League Against Hypertension Survey (FLAHS)

Abstract: Despite the availability of efficient therapies to reduce the risk of cardiovascular complications, poor adherence to antihypertensive (anti‐HTN) drugs is frequent, especially during the first year of treatment and among uncontrolled/resistant hypertensive patients. The aim of the study was to identify factors associated with adherence to anti‐HTN treatment and to examine whether they differ across sex. A total of 2743 treated hypertensive participants to the cross‐sectional Metascope survey (France, 2015) age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
9
2
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 26 publications
(64 reference statements)
1
9
2
3
Order By: Relevance
“…Females achieved BP goals more often, regardless of chosen standard, which may be related to higher adherence to antihypertensive treatment [24]. Patients who achieved BP goals had the similar age, BMI, CKD and HTN duration, and DM prevalence as the whole cohort of hypertensive patients.…”
Section: Discussionmentioning
confidence: 93%
“…Females achieved BP goals more often, regardless of chosen standard, which may be related to higher adherence to antihypertensive treatment [24]. Patients who achieved BP goals had the similar age, BMI, CKD and HTN duration, and DM prevalence as the whole cohort of hypertensive patients.…”
Section: Discussionmentioning
confidence: 93%
“…However, Berntson et al reported that depression, as defined by the PHQ‐9, was not associated with self‐reported poorer adherence to antihypertensive drugs or cholesterol‐lowering drugs in a large sample representative of the US population (the 2005‐2010 National Health and Nutrition Examination Survey) . In the study reported in this Journal, a study of Japanese patients with CVD, more than 2× daily dosing frequency, age <65 years, and active employment were significantly associated with nonadherence (OR 4.42 CI 3.02‐6.48; 1.7 CI 1.23‐2.35, and 1.43 CI1.03‐1.99), respectively; but, depression was not a significant factor in nonadherence …”
mentioning
confidence: 89%
“…In the current issue of JCC, Lefort et al report on gender differences in adherence to antihypertensive treatment in a study of French men and women >55 years of age . (gender differences in medication adherence have not been well studied).…”
mentioning
confidence: 99%
See 2 more Smart Citations